3D technology as an effective tool for reflection simulation: The Beagle 2 lander on Mars. Issue 2 (1st December 2018) - Kuzmanova, Teodora; Higgett, Nick; Sims, Mark; Tatham, Eric; Clemmet, Jim
Beagle 2, developed for the European Space Agency's Mars Express Mission by the Beagle 2 Consortium, was due to land on Mars on 25 December 2003. After being successfully ejected from the ESA's orbiter Mars Express, followed by an attempted landing, the spacecraft failed to communicate with Earth, and the mission was presumed lost. However, in January 2015, it was announced that satellite images from NASA's Mars Reconnaissance Orbiter (MRO) indicated the possibility of a successful landing by Beagle 2. In the light of these findings and the considerable uncertainty still surrounding the outcome of the mission, a team of researchers from De Montfort University and the University of Leicester have joined in a collaborative project aimed at identifying whether the object captured by NASA's HiRISE camera is Beagle 2, and detecting its possible landing configuration. The practical scientific experiment employed the innovative concept of 'reflection analysis', propounded by Dr Mark Sims – former Beagle 2 Mission Manager and professor of astrobiology and Space Instrumentation at the Space Research Centre, University of Leicester. The technique stemmed from the idea of simulating possible configurations of the Beagle 2 lander, testing how they reflect light and comparing the 3D renders to unprocessed images, available from the MRO's HiRISE camera at a number of different sun angles. De Montfort University's team used commercial 3D modelling technology to create a 3D model of the spacecraft and replicate virtually the sun angles at the times the satellite images were taken. This allowed a comparison of the simulated 3D renders to the satellite images to estimate the configuration of Beagle 2 on Mars. The results revealed that Beagle 2 probably deployed at least three, and possibly all four of its solar panels after landing on the planet's surface.